2005
DOI: 10.1080/09687630412331315125
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cannabis: Young people talking about how parents respond to their use of these two drugs

Abstract: In recent years, there has been increasing concern over rising levels of alcohol and cannabis use among young people. This paper reports findings from a qualitative investigation of young people's cannabis-related beliefs and behaviour. Fifty-nine boys and girls aged 13 to 15 years were interviewed, mostly in self-selected friendship pairs, in six contrasting locations in east central Scotland. This paper explores how young people talked about their parents' responses, actual and anticipated, to knowledge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In terms of alcohol use, parents feel that it is necessary to negotiate boundaries around drinking behaviour, preferring to use a harm reduction than an abstinence based approach (Bourdeau et al, 2012;Highet, 2005;Sherriff et al, 2008). As might be expected, such an approach does not extend to smoking and drug use, when adolescents are specifically told not to engage in these behaviours (Highet, 2005;Levy et al, 2010;Maggi et al, 2014). In six studies, parents reported a range of issues when communicating with their children about substance use.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of alcohol use, parents feel that it is necessary to negotiate boundaries around drinking behaviour, preferring to use a harm reduction than an abstinence based approach (Bourdeau et al, 2012;Highet, 2005;Sherriff et al, 2008). As might be expected, such an approach does not extend to smoking and drug use, when adolescents are specifically told not to engage in these behaviours (Highet, 2005;Levy et al, 2010;Maggi et al, 2014). In six studies, parents reported a range of issues when communicating with their children about substance use.…”
Section: Resultsmentioning
confidence: 99%
“…The way in which parents talk to their children about substance use is crucial; when they are perceived as lecturing them, adolescents are often unreceptive and do not assimilate these messages (Guilamo-Ramos et al, 2008;Levy et al, 2010;Maggi et al, 2014;Metzger et al, 2013;Sherriff et al, 2008). Having constructive conversations in which parents and children participate equally appears to be more effective (Chaplin et al, 2014;Highet, 2005). When conversations are open and involve discussions rather than lectures, adolescents feel more comfortable and report lower rates of substance use (Chaplin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations